Differences between Res Trading and Holcim Cement Bangladesh in case of SWOT analysis - Nitu, Sourav Kanti Sikder (BRAC University, 2016)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Master of Business Administration, 2015.